Molecular Investigations of the Newly Synthesized Azomethines as Antioxidants: Theoretical and Experimental Studies - Shahab, Siyamak; Sheikhi, Masoome; Filippovich, Liudmila; Dikusar, Evgenij; Pazniak, Anhelina; Rouhani, Morteza; Kumar, Rakesh (Current Molecular Medicine, 2019)
Background: In this study, the antioxidant property of new synthesized azomethins has been investigated as theoretical and experimental. Methods and Results: Density functional theory (DFT) was employed to investigate the Bond Dissociation Enthalpy (BDE), Mulliken Charges, NBO analysis, Ionization Potential (IP), Electron Affinities (EA), HOMO and LUMO energies, Hardness (η), Softness (S), Electronegativity (μ), Electrophilic Index (ω), Electron Donating Power (ω-), Electron Accepting Power (ω+) and Energy Gap (Eg) in order to deduce scavenging action of the two new synthesized azomethines (FD-1 and FD-2). Spin density calculations and NBO analysis were also carried out to understand the antioxidant activity mechanism. Comparison of BDE of FD-1 and FD-2 indicate the weal antioxidant potential of these structures. Conclusion: FD-1 and FD-2 have very high antioxidant potential due to the planarity and formation of intramolecular hydrogen bonds.
Keywords: intramolecular hydrogen bonds